An Integration of Neoclassical Growth Theory and Economic Structural Change with Monopolistic Competition Theory - Zhang, Wei-Bin (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Wealth accumulation is a deterministic factor mechanism of national economic growth. Neoclassical growth theory is basically concerned with capital and wealth accumulation in perfectly competitive market. Global markets are characterized by a great variety of markets. Nevertheless, there only a few rigorous models of wealth accumulation with other types of markets within neoclassical growth framework. This study attempts to contribute literature of economic growth by introducing monopolistic competition and monopoly into neoclassical growth theory. The model is based on a few well-established economic theories. The model is constructed within framework of the Solow-Uzawa two-sector neoclassical growth model. The description of to monopolistic competition is influenced by the Dixit-Stiglitz model of monopolistic competition. The modelling of monopoly is based on monopoly theory. We model behavior of the household with Zhang’s utility function and concepts of current income and disposable income. The unique contribution of this research is to integrate these theories in a comprehensive framework. We construct the basic model and then analyze properties of the model. The existence of a unique equilibrium point is identified by simulation. The effects of changes in some parameters comparative static analyses in some parameters.